The challenge of responsible dispensing: formal education versus professional practice (Brazilian Journal of Pharmaceutical Sciences, 2011)
The aim of the present study was to evaluate the education of Pharmaceutical Technicians for the activity of responsible dispensing. Based on a questionnaire with open and closed questions, the study sought to characterize the students, identify knowledge and attitudes regarding the Rational Use of Medications while addressing the limits and possibilities of professional and ethical dispensing in practice. In addition, a group dynamics session - focus group - was held as a forum for debate on responsible dispensing. The results showed that students tended to be mature, currently employed and were predominately women. Displaying adequate knowledge on Rational Use of Medications and of the corresponding legislation, the students reported difficulties exercising compatible practice. While the diagnosis pointed to the need for student preparation to enable ethical dispensing, the Focus Group highlighted the possibility for inclusion of a forum for reflection and debate on the ethics of dispensing as part of the Pharmaceutical Technician training.